The effect of carbohydrates on nutritional preference and development of Mediterranean flour mouth, Ephestia kuehniella Zeller (Lepidoptera: Pyralidae). (May 2020) - Kılcı, Leyla; Altun, Nurver
Abstract: In this study, the effect of different carbohydrates on food consumption, growth and development duration of Ephestia kuehniella Zeller (Lepidoptera:Pyralidae) larvae was investigated. 13 diets containing different carbohydrates were prepared. Control diet did not contain carbohydrates. The 8 diet contains 3% concentration of glucose, galactose, maltose, starch, arabinose, mannose, sucrose or fructose. 2 of the diets contains 10% or 30% starch. 2 of the diets contain a mixture of carbohydrates (2 Glucose: 1Fructose; 2 Fructose: 1 Glucose). According to the results, only the increase in food consumption does not indicate that a carbohydrate is a feeding stimulus. The conversion of carbohydrates is also important. Although the dietary consumption of arabinose is high, pupa dry weight, pupa lipid and pupa protein are not high. Conversely, although the consumption of the glucose-containing diet is low, the pupa dry weight and pupa lipid content are high. The glucose-fructose mixture is stimulant for E. kuehniella larvae. G2-F1 diet is the diet with high food consumption and growth performance. In addition, it was determined that as the starch concentration in the diet increased, the amount of consumption increased but the pupa dry weight, which is an indicator of fecundity, decreased. It is important result that the amount of pupa protein does not differ in diets except carbohydrate free diet and G2-F1 diet. Highlights: The lowest RGR value was detected in the diet containing 30% starch. Arabinose, galactose and 30% starch caused the decreasing of pupa mass. The larvae fed with arabinose have high RCR values. The increase in the starch concentration of the diet caused a decrease in the development performance of E. kuehniella .